2014
DOI: 10.5901/mjss.2014.v5n20p621
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between International Trade and Economic Growth: A Cointegration Analysis for Zimbabwe

Abstract: The relationship between trade and economic growth has continued to dominate the debate in trade and development economics. Generally, countries which trade more have been seen to have a high growth path, some of which has been attributed to trade. However, it is very difficult to attribute much of the growth to trade and trade openness. The focus of this research paper is therefore to investigate if there exists a long run relationship between various trade and other macroeconomic variables for Zimbabwe for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
11
1
Order By: Relevance
“…Our finding is consistent with (Polat et al, 2015). On the other hand, the result is inconsistent with the findings by (Asiedu, 2013;Caleb et al, 2014;Chang & Mendy, 2012;Ehigiamusoe & Lean, 2018;Hossain & Mitra, 2013). Furthermore, the result also does not congruent with the theoretical hypothesis that international trade enhances economic prosperity.…”
Section: Pooled Ordinary Least Squares (Pols) Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding is consistent with (Polat et al, 2015). On the other hand, the result is inconsistent with the findings by (Asiedu, 2013;Caleb et al, 2014;Chang & Mendy, 2012;Ehigiamusoe & Lean, 2018;Hossain & Mitra, 2013). Furthermore, the result also does not congruent with the theoretical hypothesis that international trade enhances economic prosperity.…”
Section: Pooled Ordinary Least Squares (Pols) Resultscontrasting
confidence: 99%
“…TRADE exhibits a positive and statistically significant impact on economic growth in models 1 and 3 at a 1% significance level on average ceteris paribus. As noted by (Caleb et al, 2014;Chang & Mendy, 2012;Ehigiamusoe & Lean, 2018;Hossain & Mitra, 2013), international trade has the potential to boost economic growth. This study's results appeared to be in line with the previous results from the literature and the propositions of the mercantilist, classical, and the Heckscher-Ohlin theories of trade.…”
Section: System Gmm Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have studied determinants of economic growth emphasizing a spatial econometric approach (LeSage and Fischer 2008;Olejnik 2008;Fischer et al 2009;Tian, Wang, and Chen 2010;Ramos, Suriñach, and Artís 2010;Lee and Yu 2012;Yu Ho, Wang, and Yu 2013;Caleb, Mazanai, and Dhoro 2014;Benos, Karagiannis, and Karkalakos 2015; Zahonogo 2016; Ahmad and Hall 2017) and obtained important results for the analysis of regional growth mechanisms. Their research has shown that the spatial effect favours economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…High and low-income countries have conducted research that analyzes the causal relationship between international trade and economic growth. International trade has an optimal influence on a country's economic growth (Javed, Qaiser, Mushtaq, Saif-ullaha, & Iqbal, 2012); (Caleb, Mazanai, & Netsai L, 2014); (Mogoe & Mongale, 2014) (TAPŞIN, 2015); (Abdullahi, Safiyanu, & Soja, 2016).…”
Section: Introductionmentioning
confidence: 99%